2015
DOI: 10.1103/physrevc.92.011901
|View full text |Cite
|
Sign up to set email alerts
|

Alternative ansatz to wounded nucleon and binary collision scaling in high-energy nuclear collisions

Abstract: We introduce T R ENTo, a new parametric initial condition model for high-energy nuclear collisions based on eikonal entropy deposition via a "reduced thickness" function. The model simultaneously describes experimental proton-proton, proton-nucleus, and nucleus-nucleus multiplicity distributions, and generates nucleus-nucleus eccentricity harmonics consistent with experimental flow constraints. In addition, the model is compatible with ultra-central uranium-uranium data unlike existing models that include bina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
377
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 420 publications
(408 citation statements)
references
References 47 publications
12
377
0
3
Order By: Relevance
“…At low p T (p T < 2 GeV/c), flow coefficients are expected to be mostly determined by the collective expansion of the system, which is commonly described by hydrodynamic models. The measurements are compared to three calculations, one employing IP-Glasma initial conditions [60] matched to the MUSIC viscous hydrodynamic code [61] and two calculations using iEBE-VISHNU viscous hydrodynamic code [62] with AMPT [63] or TRENTo [64] initial conditions. The parameters of TRENTo were tuned to reproduce previous measurements in Pb-Pb collisions at √ s NN = 2.76 TeV [16]; with such tuning TRENTo has been shown [64] to effectively mimic IP-Glasma initial conditions and therefore the two calculations TRENTo+iEBE-VISHNU and IP-Glasma+MUSIC are expected to be based on similar initial conditions.…”
Section: Jhep07(2018)103mentioning
confidence: 99%
“…At low p T (p T < 2 GeV/c), flow coefficients are expected to be mostly determined by the collective expansion of the system, which is commonly described by hydrodynamic models. The measurements are compared to three calculations, one employing IP-Glasma initial conditions [60] matched to the MUSIC viscous hydrodynamic code [61] and two calculations using iEBE-VISHNU viscous hydrodynamic code [62] with AMPT [63] or TRENTo [64] initial conditions. The parameters of TRENTo were tuned to reproduce previous measurements in Pb-Pb collisions at √ s NN = 2.76 TeV [16]; with such tuning TRENTo has been shown [64] to effectively mimic IP-Glasma initial conditions and therefore the two calculations TRENTo+iEBE-VISHNU and IP-Glasma+MUSIC are expected to be based on similar initial conditions.…”
Section: Jhep07(2018)103mentioning
confidence: 99%
“…Both models include saturation effects and lead to similar energy deposition in the transverse plane. In [24] it was shown that the relevant feature to describe the experimental data is that the initial entropy density is proportional to the product of thickness functions.…”
Section: B Relevance Of Initial State Fluctuations For Data Interprementioning
confidence: 99%
“…In conclusion the strangenesss production in AA, pp and pA in high energy collisions suggests a universal behavior which emerges by taking into account the transverse size of the systems and its fluctuactions in high multiplicity events. However, in events with large fluctuactions of the gluon field in the initial configuration the transverse size of small systems is model dependent [16] and therefore a more complete analysis, which takes into account ALICE data at higher energy [17], is in progress. …”
Section: Pos(eps-hep2017)158mentioning
confidence: 99%